"A Pap smear saved my life": Personal experiences of cervical abnormalities shape attitudes to cervical screening renewal. (December 2020) - Obermair, Helena M; McCaffery, Kirsten J; Dodd, Rachael H
Objective: In 2017, the Australian National Cervical Screening Program changed from two-yearly Pap smears between ages 18 and 69, to five-yearly human papillomavirus screening between ages 25 and 74 (the "Renewal"). This study investigated attitudes towards the changes, among individuals previously affected by cervical abnormalities/cervical cancer, personally or through a friend/relative. Methods: We conducted a thematic analysis of comments expressing personal history or a family/friend history of cervical abnormalities/cervical cancer as a reason for opposing changes to the cervical screening program. The comments were taken from a 20% random sample of 19, 633 comments posted on the "Change.org" petition "Stop May 1st Changes to Pap Smears – Save Women's Lives" in February–March 2017. Results: There were 831 (20.8%) commenters who reported that they were concerned about a change in screening due to: feelings of increased personal vulnerability to cervical cancer due to their own personal history of cervical abnormalities; comparison of extended screening intervals and later age of first screening to their own experiences; and a perception of increased personal risk due to family history. Conclusion: Women previously affected by cervical abnormalities or cervical cancer, personally or through a friend/relative, expressed concern about changes to cervical screening due to perceived increased risk and feeling vulnerable due to personal history.